2019
DOI: 10.3390/ijms21010195
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype in SERPINA1 (AAT) Is Associated with Reduced Risk for COPD in a Mexican Mestizo Population

Abstract: Protease inhibitor S (PiS) and protease inhibitor Z (PiZ) variants in the SERPINA1 gene are the main genetics factors associated with COPD; however, investigations about other polymorphisms are scanty. The aim of this study was to evaluate two missense single nucleotide polymorphisms (SNPs) (rs709932 and rs1303) in the SERPINA1 gene in Mexican mestizo patients with chronic obstructive pulmonary disease (COPD) related to tobacco smoking and biomass-burning exposure. 1700 subjects were genotyped and divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…This information is particularly relevant in the Mexican cohort of women whose average height is 148 cm, which is notably lower than smokers (men and women) studied by Burrows. In this sense, studies performed in women exposed to biomass showed that genetic susceptibility (57)(58)(59)(60) together with the socioeconomic context may influence growth and decrease lung function, as previously demonstrated by some reports (61)(62)(63).…”
Section: Discussionsupporting
confidence: 52%
“…This information is particularly relevant in the Mexican cohort of women whose average height is 148 cm, which is notably lower than smokers (men and women) studied by Burrows. In this sense, studies performed in women exposed to biomass showed that genetic susceptibility (57)(58)(59)(60) together with the socioeconomic context may influence growth and decrease lung function, as previously demonstrated by some reports (61)(62)(63).…”
Section: Discussionsupporting
confidence: 52%
“…33 In the present study, we observe that the minor allele (T) of rs17580 (PiS) is associated with COPD in both comparisons, tobacco smoking, and exposure to biomass-burning smoke. This polymorphism was reported by our workgroup associated with lower values in lung function among smokers, 27 but not with the genetic susceptibility to the disease, probably due to small sample size; current analysis in addition to twocomparisons with two different risk exposure factors includes a better case-control ratio, almost 1:3 in each comparison. These results lead us to the question about the frequency of risk alleles among Mexican people, in which ancestral contribution has been marked by an admixture between Caucasian and indigenous (Amerindian) populations.…”
Section: Discussionmentioning
confidence: 55%
“…In the current study, we have assessed the genetic susceptibility associated with PiS and PiZ variants evaluated by molecular techniques that let us know the state of genotypes for each protein variant. Previously, among smokers, we found the rs17580 AT genotype associated with a decreased FEV 1 /FVC ratio compared to subjects with the homozygous AA genotype, 27 and recently, two SNPs (rs709932 and rs1303) in the SERPINA1 gene too, forming a haplotype shaped by both common alleles (CT haplotype) associated with reduced risk for COPD. 28 However, investigations have focused on the PiS and PiZ variants; individuals SS, SZ, and ZZ express serum concentrations of 85%, 25%, and 15% of the protein, respectively, compared to the normal levels (MM phenotype).…”
Section: Discussionmentioning
confidence: 86%
“…Hypomethylation of SERPINA1 and fucosyltransferase-7 ( FUT7 ) genes was found to be closely related to COPD and pulmonary dysfunction. Recently, the haplotypes of two major alleles of SERPINA1 were found to be related to reduced risk of COPD ( Ponce-Gallegos et al, 2019 ). SERPINA1 gene encodes a sialic acid protein called α-1 antitrypsin (AAT), whose main function is to protect the lower respiratory tract from degradation by neutrophil elastase ( Salahuddin, 2010 ).…”
Section: Biomarker In Bloodmentioning
confidence: 99%